Analisis Faktor – Faktor Penggunaan Aplikasi Mobile Dalam Meningkatkan Jasa Layanan Terhadap Lembaga Keuangan Mikro Syariah - Saiful Bakhri; Aunur rofiq; Dikril Faizun (Program Studi Perbankan Syariah Sekolah Tinggi Agama Islam Salahuddin Pasuruan, 2022)
The type of research used in this study is a qualitative method. This study aims to analyze the factors that influence members in the use of mobile application services BMT UGT Nusantara with qualitative descriptive method. The results of the study indicate that there are factors that influence members in using the UGT Mobile application, namely it is easier to use than mobile banking in a number of banks, safer because it is easy to communicate and handle complaints, thereby cutting transportation costs, A sense of belonging arises because as a member automatically as a member as a member. the owner of the cooperative, according to the cooperative spirit of kinship. BMT UGT members are less than optimal in using the UGT Mobile application due to a lack of knowledge about the UGT Mobile application. It is necessary to conduct periodic surveys to members as evaluation material to find out whether the services and facilities provided by KSPPS BMT UGT Sidogiri Nusantara are in accordance with the expectations of members.